Madame B. : L’analyse cinématographique d’un roman - Mieke Bal (Flaubert: Revue Critique et Génétique)
Film analysis of a novelThis article investigates how the creative act can become an analytical method. Film making requires another kind of reading. The Madame B. project, in which Mieke Bal and Michelle Williams Gamaker have created a series of video installation pieces based on Madame Bovary, is, amongst other things, an approach to the novel in its audio-visualization, apart from its narration. The current relevance of the damage done by the combination of Capitalism and romantic love, that exchange their main characteristics, is the background political theme. This study takes Emma’s death scene as an example, examining the links between film options and ethical issues.